NUMERICAL MODELLING OF CHICKEN-FOOT FOUNDATION - Vipman Tandjiria (Institute of Research and Community Outreach - Petra Christian University, 1999)
This paper presents an analysis of the chicken-foot foundation using the finite element method. The foundation is considered as a reinforced concrete slab resting on a number of reinforced concrete pipes filled with and surrounded by in-situ soil. The soil and the pipes were modelled by isoparametric solid elements while the slab was modelled by isoparametric thick-plate elements. The study was intended to illustrate the basic mechanism of the chicken-foot foundation. Three cases have been considered for the parametric studies. The parameters investigated are thickness of slab, length of pipes and spacing between pipes. It is shown that such a foundation improves the behaviour of the raft foundation. It is also found that all the parameters used in the parametric studies influence the behaviour of the chicken-foot foundation.